Characteristics of quiescent adult neural stem cells induced by the bFGF/BMP4 combination or BMP4 alone in vitro - Xu, Sutong; Zhang, Xi; Li, Zhuoqun; Liu, Chenming; Liu, Qiulu; Chai, Huazhen; Yao, Hongkai; Luo, Yuping; Li, Siguang; Li, Chun (Frontiers in Cellular Neuroscience, 2024)
Bone morphogenetic protein-4 (BMP4) is involved in regulation of neural stem cells (NSCs) proliferation, differentiation, migration and survival. It was previously thought that the treatment of NSCs with BMP4 alone induces astrocytes, whereas the treatment of NSCs with the bFGF/BMP4 combination induces quiescent neural stem cells (qNSCs). In this study, we performed bulk RNA sequencing (RNA-Seq) to compare the transcriptome profiles of BMP4-treated NSCs and bFGF/BMP4-treated NSCs, and found that both NSCs treated by these two methods were Sox2 positive qNSCs which were able to generate neurospheres. However, NSCs treated by those two methods exhibited different characteristics in state and the potential for neuronal differentiation based on transcriptome analysis and experimental results. We found that BMP4-treated NSCs tended to be in a deeper quiescent state than bFGF/BMP4-treated NSCs as the percentage of ki67-positive cells were lower in BMP4-treated NSCs. And after exposure to differentiated environment, bFGF/BMP4-treated NSCs generated more DCX-positive immature neurons and MAP2-positive neurons than BMP4-treated NSCs. Our study characterized qNSCs treated with BMP4 alone and bFGF/BMP4 combination, providing a reference for the scientific use of BMP4 and bFGF/BMP4-induced qNSCs models.